(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2019)
Experimental work has been conducted using silica oxide SiO2 nanoparticle as anadditive to diesel fuel in a compression ignition engine in order to reduce pollutantsemissions and to improve engine performance. A 10 ppm and 20 ppm of SiO2 nanoparticleis added to the diesel fuel. The results showed that the SiO2 nanoparticle blended with dieselfuel improve engine performance such as brake thermal efficiency and brake specific fuelconsumption, increase in exhaust gas temperature and reduces carbon monoxide, andunburned hydrocarbon emissions. Also the results showed that the blend of the SiO2nanoparticle to diesel fuel led to increase in the carbon dioxide in the exhaust gases. Thetests are carried out at constant speed of 1500 rpm, under different engine load conditions.